The NHRC Water Database for Planning and Research. - Soriano, Roberto S.
The NHRC Water Database is a collection of hydrologic, hydrogeologic and geologic data and other water related data and information on the Metro Manila and the Laguna Lake Basins. Gathered through the course of the three year IDRC-funded research study "Water Resources Management Model for Metro Manila" undertaken by the NHRC, the data and information were contributed by the MWSS, MGB, EMB, LLDA, UP NIGS, UP University Library, LWUA, NAMRIA, PAGASA, BSWM, DPWH, DOH and OEA. The processing and analysis of the data and information were primarily aimed at obtaining the inputs to the Conjunctive Use Water Resources Management Model or CUWARM. Digitized maps (e.g. soil type, land cover, geology, drainage basin definitions), contour plots (e.g. topography, geologic basement, mean annual rainfall, piezometric levels), statistical parameters and plots of time series data (e.g. rainfall, streamflow, groundwater level), and well lithologic logs are some of the computer generated outputs from the database. Through the database, water related information can readily be accessed and processed to facilitate various research or planning activities by NHRC and other interested parties or agencies.